Multidisciplinary stakeholder engagement in a type 2 diabetes comparative effectiveness study utilizing real-world data - Elizabeth H. Golembiewski; Mindy M. Mickelson; Juan P. Brito; Victor M. Montori; Rozalina G. McCoy (Journal of Clinical and Translational Science)
Abstract